Facing challenges of COVID-19 on dental education in Sri Lanka - Indika Priyanthi Thilakumara; Rasika Manori Jayasinghe; Ruwan Duminda Jayasinghe (Journal of Multidisciplinary Dental Research)
Second wave of COVID 19 pandemic in Sri Lanka has given rise to multiple challenges in all the sectors and higher education is not spared. Even though there are multiple challenges in effective delivery of education, Faculty of Dental Sciences, University of Peradeniya being the only institute providing undergraduate dental education in Sri Lanka and operated totally free of charge for students has also taken important steps to face the emerging challenges and make timely modifications to teaching and learning methods to ensure the undergraduates achieve the required competency levels without unwarranted risk. As a major change, effectiveness of tele-dentistry has been recognized. COVID-19 pandemic has demonstrated that there is a severe underutilization of e-learning as an educational tool and the issues with technology and lack of facilities. It has created an environment for all of us to see the dental education in a different perspective and to identify the need for a transformation. It is obvious that the way we practice dentistry and deliver dental education has significantly changed as a result of the COVID-19 pandemic and became a major challenge for us as the dental education in the country is provided free of charge and with limited resources. This opportunity is to be used to review clinical practices including safety measures, dental curricula, teaching and assessment tools to serve the next generation of patients and dentists. Practicing dentistry in pandemics of this nature should undoubtedly be part of the dental education in the future. Keywords: Covid-19; dental education; pandemic; Sri Lanka